Modeling of oxygen permeation through filled polymeric layers for barrier coatings. Issue 20 (2nd February 2017) - Nyflött, Åsa; Petkova‐Olsson, Yana; Moons, Ellen; Bonnerup, Chris; Järnström, Lars; Carlsson, Gunilla; Lestelius, Magnus; Minelli, Matteo
ABSTRACT: This paper presents an extended model for gas permeation through a filled polymer layer, and it is applied to the case of oxygen permeability through a poly(vinyl alcohol)/kaolin dispersion coating. The model is based on a description of polymer and penetrant properties in a thermodynamically consistent framework. The gradient in chemical potential is considered the driving force for the diffusion of the penetrating gas. The well‐established nonequilibrium lattice fluid (NELF) model for the polymer phase is extended in order to account for the additional features of the polymer/filler system, such as the concentration and aspect ratio of the inorganic filler, which enhance the penetrant tortuosity. The model predicts the behavior of penetrant permeability with respect to polymer crystallinity and filler fraction. The calculated results are compared to experimentally obtained data for oxygen permeability through a dispersion coating layer consisting of poly(vinyl alcohol) (PVOH) and two types of kaolin with different aspect ratios. A good agreement is found in terms of the effects of polymer crystallinity, filler concentration, and filler aspect ratio. The experimental results also indicate a complex interplay between the polymer and the filler as the permeability of two differently surface modified kaolin clays was determined, displaying slight deviations from model predictions. Significant differences were observed in the experimental results between the two fillers investigated, and the one characterized by the smaller aspect ratio affects to a minor extent the oxygen permeability, as illustrated by the model. Furthermore, the lower hydrolysis degree of PVOH gives a reduced barrier performance, as expected. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44834. Abstract :